2016
DOI: 10.3847/0004-637x/832/2/195
|View full text |Cite
|
Sign up to set email alerts
|

Heating Mechanisms in the Low Solar Atmosphere Through Magnetic Reconnection in Current Sheets

Abstract: We simulate several magnetic reconnection processes in the low solar chromosphere/photosphere, the radiation cooling, heat conduction and ambipolar diffusion are all included. Our numerical results indicate that both the high temperature( 8 × 10 4

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
111
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 51 publications
(77 reference statements)
11
111
1
1
Order By: Relevance
“…The maximum plasma temperature is above 5 × 10 4 K during the later stage of the reconnection process, which is much higher than that in Case A. These results are consistent with the previous one fluid MHD simulations (Ni et al 2016), where the plasmas were heated from 4200 K to very high temperatures (about 8×10 4 K) with reconnection magnetic fields of 500 G at around the TMR region in that work. However, it is not realistic to have such high temperatures and weakly ionized hydrogen plasmas, which is a reflection of the unphysical nature of the ionization-recombination balance imposed in this calculation.…”
Section: The Non-equilibrium Ionization-recombination Effect In Initisupporting
confidence: 91%
See 1 more Smart Citation
“…The maximum plasma temperature is above 5 × 10 4 K during the later stage of the reconnection process, which is much higher than that in Case A. These results are consistent with the previous one fluid MHD simulations (Ni et al 2016), where the plasmas were heated from 4200 K to very high temperatures (about 8×10 4 K) with reconnection magnetic fields of 500 G at around the TMR region in that work. However, it is not realistic to have such high temperatures and weakly ionized hydrogen plasmas, which is a reflection of the unphysical nature of the ionization-recombination balance imposed in this calculation.…”
Section: The Non-equilibrium Ionization-recombination Effect In Initisupporting
confidence: 91%
“…Their semi-empirical modeling showed that a higher temperature (higher than 10 4 K) was not compatible with observed Hα and Ca II 8542Å line profiles and that higher temperatures would be inconsistent with observations. Many numerical simulations (e.g., Chen et al 2001;Isobe et al 2007;Archontis & Hood 2009;Xu et al 2011) showed that the maximum temperature increases in magnetic reconnection below the upper chromosphere is always only several thousand K. However, the work by Ni et al (2016) showed that the plasma can be heated from 4200 K to above 8 × 10 4 K during magnetic reconnection in the TMR with strong magnetic field and low plasma β (Ni et al 2016). These simulations included ambipolar diffusion, temperature dependent magnetic diffusion, heat conduction, the optically thin radiative cooling deduced from observations (Gan & Fang 1990) and a heating term, but the plasma was assumed to be in a steady ionization equilibrium state.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the methodology of Innes et al (2015) and Guo et al (2017), we create the synthetic spectral line profiles that might be observed in the reconnection region in the lower atmospheric environments according to the numerical experiment of Ni et al (2016). Ni et al (2016) performed MHD numerical experiments for magnetic reconnection occurring in the temperature minimum region (TMR) and the low chromosphere by including the radiation cooling, the heat conduction, and the ambipolar diffusion. Their results indicated that the plasma could be heated from several 10 3 up to 10 5 K by magnetic reconnection in which the slow-and the fast-mode shocks around the plasmoids formed.…”
Section: Synthetic Spectral Line Profiles Created According To Numerimentioning
confidence: 99%
“…With the development of the observational technology, more and more features of magnetic reconnection were reported (Savage et al 2010;Liu et al 2010;Zhang et al 2012;Sun et al 2012;Savage et al 2012aSavage et al , 2012bSu et al 2013;Zhang et al 2013;Deng et al 2013;Dudík et al 2014;Tian et al 2014;Yang, Zhang & Xiang 2015;Sun et al 2015;Xue et al 2016;Li et al 2016;Zhu et al 2016;Li et al 2017;Shen et al 2017). Furthermore, many simulations also show evidence that magnetic reconnection plays an important role in solar eruptions (Antiochos et al 1999, Chen & Shibata 2000, Amari et al 2003, Aulanier et al 2010, Janvier et al 2013Ni et al 2016Ni et al , 2017Mei et al 2017;Jiang et al 2016Jiang et al , 2017.…”
Section: Introductionmentioning
confidence: 99%